Robust static output feedback H control for uncertain Takagi-Sugeno fuzzy systems - Elias, Leandro Jose; Faria, Flavio Andrade; Araujo, R.; Magossi, Rafael; Oliveira, Vilma Alves (Institute of Electrical and Electronics Engineers (IEEE), 2022)
In this work, a robust static output feedback (SOF) design for continuous-time nonlinear systems under norm bounded uncertainties, described as a Takagi-Sugeno (TS) system is proposed. The key features are that a switching control law is used to activate the SOF gains to stabilize the uncertain TS fuzzy system and that the SOF design does not require the measurements of all premise variables in real time as in the standard fuzzy parallel distributed compensation (PDC) design. The main result is given in terms of linear matrix inequalities (LMIs) which guarantees a H attenuation level of for the SOF control system. The efficiency of the main results is illustrated with examples, including a nonlinear active suspension system under uncertain driver masses, and compared to other published results from the literature.
Keywords: Control systems; full rank factorization; Fuzzy systems; Nonlinear systems; nonlinear systems; norm bounded uncertainties; Real-time systems; Switched controller; switched fuzzy Lyapunov-like functions; Switches; Symmetric matrices; Uncertainty